Analysis of Effective Policy Strategies to Address Multidimensional Stunting Using the Biplot Method in Bengkulu Province - Regina Adelisa; Vivi Elvira Sahputri Syah; Gihon Nakata Silaen; Firdaus; Fahrulriza, Teuku; Fajariyanto, Eko; Pratama, Novrian (Journal of Statistics and Data Science, 2025)
This study aims to analyze the factors contributing to stunting in Bengkulu Province. The method used is biplot analysis, by reducing the Principal Component Analysis (PCA) dimensions into two components. A quantitative approach was employed, involving ten variables representing health, nutrition, education, housing, food security, and social protection factors. The results indicate that Bengkulu City has characteristics that are significantly different from other regencies. The key contributing factors include limited access to basic health services (particularly the availability of skilled birth attendants and immunization coverage), high levels of food insecurity, low access to proper sanitation and safe drinking water, limited practice of exclusive breastfeeding, and low utilization of government assistance programs such as BPJS Kesehatan (National Health Insurance) and KPS/KKS (Social Welfare Cards). It is expected that the findings of this study can provide valuable insights and contribute to efforts in reducing the prevalence of stunting in Bengkulu Province.